Ketidaksantunan Berekspresi Dan Daya Pragmatik Dalam Wacana Haters Politik Dan Implementasinya Sebagai Materi Ajar Bahasa Indonesia Di SMA - Ahmad, Jamaludin, Prof. Dr. Harun Joko Prayitno, M.Hum, Prof. Dr. Abdul Ngalim, M.Hum (2016)
The purpose of this study is to describe a form of politeness expression, intent pragmatic force, and its implementation as a teaching material in learning Indonesia language in the learning Indonesian. Research was conducted on speech Haters Joko Widodo on social media facebook by using qualitative descriptive methods, and uses fixed strategy (embedded research). The data collection technique using the technique see and record. The results of the 47 the data concluded that: 1) the nature impoliteness contains five form: directly impoliteness there are 6 Data or 14%, positive impoliteness 20 data, or 43%, negative impoliteness there are five data or 11%, sarcasm or apparent politeness 2 data or 4%, as well as hold as much politeness 2 data or 4%; 2) force pragmatics in speech Haters politics contains six force: force booed as much as 3 data or 6%, the force to criticize as much as 4 data or 8%, force insinuated as much as 1 data or by 2%, the force to threaten as many as 1 data or by 2%, force demand by 2 data or equal to 4%, and the urgent force as much as 1 data or by 2%; and 3) these findings can be implemented as a teaching material in class X Indonesian 2nd semester in the high school.